1997
DOI: 10.5632/jila.60.315
|View full text |Cite
|
Sign up to set email alerts
|

The Visual Impact of Building Development on Ritsurin Garden and Its Conservation

Abstract: Ritsurin garden is a prominent Japanese strolling garden located in Takamatsu City, Kagawa Prefecture, and is a listed national cultural property. However it is presently being visually spoilt by the existence of modern tall buildings bordering the garden. In this study, twelve view points were selected as observation locations. The visual impact of modern tall buildings on the garden scenery was described based on the vertical and the horizontal angles of the buildings views visible from each observation poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
8
1
1
Order By: Relevance
“…Since high-rise buildings have filled the air of the city, Daimyo Gardens had to replace their background views with those buildings. Regarding the issue, some studies have been done to analyze the visual impact of the visible surrounding buildings on traditional Japanese gardens, and the results have indicated that the visibility of external buildings have a negative impact on visual quality of the gardens and cause landscape destruction [10][11][12][13][14][15]. Besides, an empirical study has demonstrated that a majority number of the visitors of a traditional Japanese garden (Ritsurin Garden in Takamatsu city) judged the visible external buildings as causing a negative impact and they supported conservation actions for reducing the conspicuousness of the building views [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since high-rise buildings have filled the air of the city, Daimyo Gardens had to replace their background views with those buildings. Regarding the issue, some studies have been done to analyze the visual impact of the visible surrounding buildings on traditional Japanese gardens, and the results have indicated that the visibility of external buildings have a negative impact on visual quality of the gardens and cause landscape destruction [10][11][12][13][14][15]. Besides, an empirical study has demonstrated that a majority number of the visitors of a traditional Japanese garden (Ritsurin Garden in Takamatsu city) judged the visible external buildings as causing a negative impact and they supported conservation actions for reducing the conspicuousness of the building views [12].…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies about the visual impact of the high-rise building views on the traditional Japanese gardens dealt with the issue with the objective approach 138 Visitors' Perception of High-rise Building Effect on the Scenery of Traditional Gardens: A Case Study in Hama-rikyu Gardens, Tokyo [10,11,[13][14][15], but the studies gauging visitor's preference is limited [12]. In this regard, this research was conducted to understand the garden visitors' perception and convey those indices to the experts to gain a better understanding of visitor preferences.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies regarding the issue have demonstrated the negative impact of high-rise buildings on Japanese gardens. Moreover, they stated that the surroundings of the gardens need to be controlled urgently since the original spirit is under the threat of devaluation (Lin et al, 2017;Shinji, 2015;Shinobe, 2012;Koizumi and Ishikawa 2007;Arifin and Masuda, 1997;Shinji et al, 1989). However, most these studies were done with objectivist approaches whereas the research addressing the issue by considering the subjective appraisals of users is still limited (Senoglu et al, 2018;Arifin and Masuda, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The gardens of this period were a new prototype with their design features called kaiyu-shiki teien (strolling garden) and Shakkei (borrowed scenery) (Arifin, 1997). These gardens were created with a broad consideration of visual qualities and concentrated on not only internal design but also made use of remote landscapes such as Mt.…”
Section: Introductionmentioning
confidence: 99%
“…Negara di luar Indonesia khususnya Jepang memiliki perhatian yang tinggi terhadap kualitas visual sehingga setiap adanya pembangunan perlu dilakukan sebuah penilaian atau assessment [8][9] [10]. Penilaian tersebut untuk mencegah hilangnya sense terhadap lanskap sekitar.…”
unclassified